Child Care Centers' Role in Support of Breastfeeding Families. Issue 3 (May 2016) - Garth, Emily; Messer, Abigail L.; Spatz, Diane L.
Abstract: Purpose: The purpose of this study was to investigate individual child care centers' attitudes and policies related to breastfeeding in two distinct areas in Philadelphia. Little is known about individual centers' approach to breastfeeding despite returning to work being cited as a major barrier to continued breastfeeding. Study Design and Methods: Data were collected by compiling a list of child care centers in the areas of study and conducting telephone surveys of the 166 centers that met inclusion criteria. Surveys were administered using an adapted tool from the New York State Department of Health. Data were analyzed using descriptive statistics. Results: A total of 47 of the 166 (28%) of centers completed the survey. Results indicate there is room for improvement in education and training of staff on benefits of breastfeeding and human milk. The majority of centers (95%) surveyed indicated they would not feed an infant anything besides human milk unless specifically stated in a feeding plan. However, only 40% of centers had staff trained about benefits of breastfeeding and how to prepare and store human milk. Results varied between West Philadelphia and Center City. Clinical Implications: Widespread education of healthcare providers and child care center staff is necessary to ensure adherence to breastfeeding support guidelines and dissemination of accurate information to breastfeeding families. Nurses and other healthcare providers need to be aware of child care as a barrier to breastfeeding and the importance of providing comprehensive education and referral to community resources. Abstract : Very little information is known about how child care centers promote breastfeeding. This study provides information about support of breastfeeding by child care centers in the Philadelphia, PA area and has implications for all child care centers in the United States.